African vegetation studies: introduction to a Special Collection - Reginald T. Guuroh; Leslie R. Brown; Miguel Alvarez; Manfred Finckh; Ute Schmiedel; Gaolathe Tsheboeng; Jürgen Dengler (Vegetation Classification and Survey (VCS))
Abstract: This editorial introduces the Special Collection of “African Vegetation Studies”. The collection includes seven research papers from four African countries. One paper examines the impact of traditional agro-ecosystems on plant diversity in Morocco. In Benin, one research paper focuses on vegetation associations in a biosphere reserve, and another is on land cover changes on inselbergs. In Namibia, one paper provides a syntaxonomic description of the Karstveld vegetation, while another models potential vegetation changes along a south-north rainfall gradient. Two papers present research on vegetation classification and descriptions of two natural areas in South Africa, namely the Tankwa Karoo National Park and the Telperion Nature Reserve. The collection demonstrates that there are important classification studies ongoing in different parts of the continent to better understand the diversity and complexity of African vegetation. At the same time our mini-review of the current status of vegetation classification and vegetation-plot databases in Africa highlights that much work remains to be done to achieve a comprehensive and internationally consistent vegetation classification for the countries of Africa, which would be beneficial for land use management, biodiversity conservation and ecological research. Abbreviations: EVA = European Vegetation Archive; EVS = European Vegetation Survey; GDP = Gross Domestic Product; IAVS = International Association for Vegetation Science; IAVS-AS = IAVS Regional Section for Africa; VCS = Vegetation Classification and Survey.